Psychopedagogical Diagnosis: From Classifying Students to Identifying Barriers to Learning and Participation - Herrera-Rodríguez, Jose Ignacio (2022)
Objective. This work aims to reflect on the psychopedagogical diagnosis of students and their evolution from a psychometric and classificatory approach to the identification of barriers to learning and participation in inclusive schools. Analysis. An integrative review of the bibliography was carried out, structured in two stages. In the first, information was collected on the postulates of cognitive psychology, psychometric studies of intelligence, and their influence on educational practices. In contrast, the second stage was directed to the search for the postulates of social psychology and the conceptions of inclusive education. The criteria for analyzing the bibliographic information were the psychometric approach to intelligence, the biological approach, the interaction of the biological and the social in the development of the personality, the social context as a generator of barriers, the various barriers that impede learning, and student participation. Conclusions. The psychopedagogical diagnosis should focus on the pedagogical aids to move from a diagnosis based on the identification of the student’s disabilities and educational needs to a diagnosis that emphasizes the context; it should also focus on identifying those barriers that prevent learning and participation, and this from an optimistic point of view of the psychological processes in formation and sustained in the social model of inclusive education. Based on the analyzes conducted, it is advisable to organize educational processes that eliminate the barriers preventing attention to the diversity of students in inclusive schools.